2020
DOI: 10.3389/fchem.2020.00020
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study on Laser Cooling Feasibility of Group IVA Hydrides XH (X = Si, Ge, Sn, and Pb): The Role of Electronic State Crossing

Abstract: The feasibility of direct laser cooling of SiH, GeH, SnH, and PbH is investigated and assessed based upon first principles. The internally contracted multi-reference configuration interaction method with the Davidson correction is applied. Very good agreement is obtained between our computed spectroscopic constants and the available experimental data. We find that the locations of crossing point between the B 2 − and A 2 states have the tendency of moving downwards from CH to SnH relative to the bottom of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
1
9
0
1
Order By: Relevance
“…The extremely small vibrational branching loss ratios of the transition for NH and PH indicate that the intermediate electronic state will not interfere with the laser-cooling. Hence, we will construct feasible three-laser cooling schemes for NH and PH on the basis of the transition in the next section, which satisfy all known criteria including the fourth one proposed in our recent work ( Li et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extremely small vibrational branching loss ratios of the transition for NH and PH indicate that the intermediate electronic state will not interfere with the laser-cooling. Hence, we will construct feasible three-laser cooling schemes for NH and PH on the basis of the transition in the next section, which satisfy all known criteria including the fourth one proposed in our recent work ( Li et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is known ( Fu et al, 2016 ; Yuan et al, 2019 ; Li et al, 2021 ) that, a suitable candidate for laser cooling needs to satisfy three criteria: highly diagonal Franck-Condon factors (FCFs), an extremely short radiative lifetime, and no interference from the intermediate electronic states. In our recent work, the fourth criterion for molecular laser cooling was proposed, that is, no electronic-state crossing, or the crossing point between the two states was high enough in energy ( Li et al, 2020 ). Consequently, all electronic states close to those chosen for laser-cooling should be calculated and checked beforehand in selecting laser-cooling candidates.…”
Section: Introductionmentioning
confidence: 99%
“…For cancer treatment, there is a specific enzyme present in this tumor microenvironment. Therefore, by employing a carrier with a component that sensitive to the present enzyme, a control released system through enzymatic cleavage is obtained [ 199 ]. Cai et al reported on the production of enzyme responsive MSNs with chitosan as the gate responsible for trapping the drug in the MSNs pores.…”
Section: Msns As Smart Drug Delivery Agentmentioning
confidence: 99%
“…11,12 Recently, Bian proposed the fourth criterion that there should be no electronic-state crossing, or the crossing point is high enough in energy relative to the ground vibrational levels. 13 In this previous work, 13 the crossings considered are between two electronic states of the same spin multiplicity. Here, we extend the fourth criterion to the case involving the crossings between electronic-states of different spin multiplicities, where spinorbit couplings (SOCs) need to be evaluated.…”
Section: Introductionmentioning
confidence: 99%